Availability and approval of cannabis‐based medicines for chronic pain management and palliative/supportive care in Europe: A survey of the status in the chapters of the European Pain Federation. (13th November 2017) - Krcevski‐Skvarc, N.; Wells, C.; Häuser, W.
Abstract: Background: There is considerable public and political interest in the use of cannabis products for medical purposes. Methods: The task force of the European Pain Federation (EFIC) conducted a survey with its national chapters representatives on the status of approval of all types of cannabis‐based medicines, the covering of costs and the availability of a position paper of a national medical association on the use of medical cannabis for chronic pain and for symptom control in palliative/supportive care. Results: Thirty‐one out of 37 contacted councillors responded. Plant‐derived tetrahydrocannabinol/cannabidiol (THC/CBD) oromucosal spray is approved for spasticity in multiple sclerosis refractory to conventional treatment in 21 EFIC chapters. Plant‐derived THC (dronabinol) is approved for some palliative care conditions in four EFIC chapters. Synthetic THC analogue (nabilone) is approved for chemotherapy‐associated nausea and vomiting refractory to conventional treatment in four EFIC chapters'. Eight EFIC chapters' countries have an exceptional and six chapters an expanded access programme for medical cannabis. German and Israeli pain societies recommend the use of cannabis‐based medicines as third‐line drug therapies for chronic pain within a multicomponent approach. Conversely, the German medical association and a team of finish experts and officials do not recommend the prescription of medical cannabis due to the lack of high‐quality evidence of efficacy and the potential harms. Conclusions: There are marked differences between the countries represented in EFIC in the approval and availability of cannabis‐based products for medical use. EFIC countries are encouraged to collaborate with the European Medicines Agency to publish a common document on cannabis‐based medicines. Significance: There are striking differences between European countries in the availability of plant‐derived and synthetic cannabinoids and of medical cannabis for pain management and for symptom control in palliative care and in the covering of costs by health insurance companies or state social security systems. Abstract : This article is content of a special issue on cannabinoids, part of the issueEur J Pain 22:03 (2018) of the European Journal of Pain